THE Effectiveness of Giving Red Spinach Syrup to Pregnant Women With Mild Anemia Against Increase In Hb Level - Ani T Prianti; Sutrani syarif; Nurhidayat Triananingsih (Jurnal Gizi dan Kesehatan Keluarga, 2024)
Anemia in pregnant women that is not treated properly can increase the risk of dangerous complications, such as premature labor. In addition, anemia can also increase the risk of low birth weight in infants. On the mother's side, anemia can increase the risk of postpartum depression and post-saline maternal death.the effect of giving red spinach extract on increasing hemoglobin levels in pregnant women with moderate anemia on average experienced a significant increase from before and after giving red spinach extract. Anemia is a condition where your body does not have enough red blood cells whose job is to deliver oxygen to all body tissues so that these organs can work normally. As a result, you will feel symptoms of anemia such as weakness, fatigue, and lethargy. In mild and temporary conditions of anemia, you can overcome it by consuming vegetables, fruits, and drinking enough water. Consume foods that are high in iron and folic acid such as red spinach, liver, seafood, and green leafy vegetables. This study aims to determine the effectiveness of giving red spinach to increase HB levels for pregnant women with anemia by consuming red spinach. The research design used was pre-experiment with Post-Test Only Control Group Design. The population in this study were pregnant women in the working area of the Tolo 'puskesmas, Gowa Regency. the type of sampling was purposive sampling with the fulfillment of criteria, the sample size in this study was 30. The research sample in this design was Post-Test Only Control Group Design. Data collection techniques are primary data by observation (observation) directly to the respondents of this study to look for changes or things that will be examined